A panorama of linguistic landscape studies - Gorter, D. (Durk); Cenoz, Jasone (Multilingual Matters, 2023)
"This book provides an overview of how the field of Linguistic Landscape Studies has emerged and developed over the past 20 years, combined with an in-depth exploration of the theoretical approaches, innovative research methods and major themes that have been central to this dynamic area of research"--